STUDI KEPADATAN TIKUS DAN EKTOPARASIT DI DAERAH PERIMETER DAN BUFFERPELABUHAN LAUT CILACAP - Yudhy Cahyo Priyotomo; Lutfi Santoso; Martini Martini; Retno Hestiningsih (Jurnal Kesehatan Masyarakat (Undip), 2015)
Rats are rodent that harm to human life and able to adabt to the environment including port area. The increasing flow of passanger and goods through seaport need to be awareagainst the transmision of rodent borne disease in port area. The purpose is to assess the density of rat and ectoparasites in Cilacap seaport wich includes port of Tanjung Intan and fishing port of Cilacap (PPSC). The reserch was done in February 2014. This was a descriptive research used survey method with cross sectional approach. A single live trap mounted in the perimeter and buffer area with grilled coconut bait for four consecutive days.The result of the research at port of Tanjung Intan obtained species Rattus tanezumi (45%), R. norvegicus (38%) and Suncus murinus (17%). In PPSC obtained species Rattus tanezumi (37%), R. norvegicus (47%), R. norvegicus javanus (2%), Mus musculus (1%), Bandicota indica (2%) and Suncus murinus (11%). The relative density rats on Tanjung Intan is 6,6% and PPSC 13%. A kind of ectoparasites obtained in both location identified as flea of  Xenopsylla cheopis, lice of Hoplopleura oenomidis and mites of Echinolelaps echinidnus and Laelaps nuttalli. The flea index of X. cheopis on port of Tanjung Intan is 1,5 and on PPSC 1,9. Mite index in port of Tanjung Intan higher(1,05) than PPSC (0,35). Lice infestement in port of Tanjung Intan (1,9%) lower than PPSC (17,2%). The conclusion is port of Cilacap need to be alert to the possible spread of rodent and vector borne disease related to the density of rat and the ectoparasites. Rodent control in PPSC and port of Tanjung Intan need to be done.